On and off challenges and evolution of student activism in post-pandemic Philippines - Pareja, Kathryn Nicole A.; Villanueva, Isabella F.; Villarin, jose Miguel L. (College of Social Sciences, University of the Philippines Cebu, 2023)
Since the early 1960s, student activism and its related movements have occupied a permanent space within Philippine politics in addressing local and national issues; it has become increasingly prominent during the Duterte administration due to the threats and violations of human rights and is poised to continue under the Marcos-Duterte administration. As such, it has not been exempted from the administration?s crackdown on state critics, with students being threatened, red-tagged, and arrested. The COVID-19 pandemic caused an abrupt halt to in-person activism, which prompted student activism to adapt from ?offline? to online activism. As a result of the worsening social conditions and the expansion of the means of democratic participation, student activism has become more evident, but so have its pre-existing difficulties and those inherent to online activism. This paper assesses the state of student activism (i.e., its forms, challenges, and effectiveness) in private and public higher education institutions (HEIs) within Cebu City, Philippines through interviews with student activists. It seeks to address the gaps with regard to whether online activism is an impediment and/or a boon to student activism and what its trade-offs are. It analyzes such under the framework of Oliver, Marwell, & Teixeria?s Critical Mass Theory (CMT). It ultimately aims to propose an inclusive post-pandemic analytical framework of student activism. Entering the uncertain new normal necessitates an enduring system and culture of democratic participation, over which student activists have a large stake and considerable influence over.